Implementation of the Gerakan Peduli dan Berbudaya Lingkungan Hidup in Adiwiyata and Non-Adiwiyata Schools (Study of SMAN 1 Martapura and MAN 1 Banjarmasin) - Nur Mala Sari; Tuti Mutia; Sugeng Utaya; I komang Astina (Universitas Lambung Mangkurat, 2025)
Efforts to overcome environmental problems in South Kalimantan can be carried out through education with the strategy of the Environmental Care and Culture Movement in Schools (Gerakan PBLHS), schools that successfully carry out this strategy will receive an Adiwiyata award. Gerakan PBLHS is not only applied in Adiwiyata Schools, but can also be applied in Non Adiwiyata Schools. The purpose of this research is to find out the forms of implementation of the Gerakan PBLHS in Adiwiyata and Non Adiwiyata Schools and to identify the supporting factors and obstacles in the implementation of the Gerakan PBLHS. This research used descriptive qualitative methods with observation and interviews with teachers, Adiwiyata coaches, and students. The variable in this study is the Gerakan PBLHS based on the Gerakan PBLHS guidebook. The implementation of the Gerakan PBLHS at SMAN 1 Martapura is the integration of Gerakan PBLHS with learning, greening, and Green House, 3R waste management, and clean Friday. Meanwhile, the implementation of the Gerakan PBLHS at MAN 1 Banjarmasin is a ban on the use of plastic bags, clean Friday, and Waste Bank.